Resisting Religious Trauma and the Stultification of Queer Subjectivities in Chinelo Okparanta’s Under the Udala Trees - Wisani Mushwana (The Thinker)
In Nigeria, politics is intricately linked to religion to such an extent that political leaders have relied on religious doctrine to criminalise same-sex relations and legitimise the country’s queerphobic policies. This paper examines Chinelo Okparanta’s Under the Udala Trees (2015) to demonstrate the ways in which Nigerian political leaders weaponise what Myra Mendible (2016) calls “stigmatised shame” in their efforts to deter the manifestation of queer identities and to render queer subjectivities docile. Focusing on Okparanta’s main character, Ijeoma, I explore the ways in which she resists docility enforced through Bible lessons and imagines queer freedom through a subverted reading of biblical scriptures. I argue that this subversion of scriptures often widely read as condemnation of queer subjectivities illuminates ways in which their normative interpretations are confined to adopted imperial heteronormative formulations. I further argue that Ijeoma’s subverted reading highlights Christian theology’s intentional resistance to understanding conceptual resources needed in the formulation of well-rounded queer subjectivities—an understanding that would espouse their legitimacy—and in turn delineates them to condemnation. I contend that the novel’s interrogation of shame, weaponised through biblical scriptures and inherent in contemporary conceptual resources that inform Christian ideology, intercepts its effects that lead to religious traumatisation.